Politics, Participation & Power Relations
VI, 205 p.
Keywords: Until recently, youth have become the great absence regarding matters of citizenship, justice, and democracy. Rarely are young people taken up with the important discourses of freedom and citizenship, especially discourses that transcend national boundaries and academic disciplines. Richard Mitchell and Shannon Moore have put together a brilliant book that not only fills this void, but makes one of the most powerful cases I have read for addressing young people in terms that not only allow them to talk back, be heard, but also to enjoy those rights and freedoms that give democracy a real claim on its ideals and promises. Every educator, parent, student, and all those young people now making their voices heard all over the world should read this book. Henry A. Giroux This diverse collection will appeal to students in senior undergraduate and graduate courses looking into the new cosmopolitanism in social policy, citizenship or cultural studies, in child and youth studies, and in post-colonial approaches to education, sociology, and political science.